A Modern, Rational Jeremiad - Smith, David H. (The Hastings Center report, 2017)
I have been a Daniel Callahan reader for over thirty years. My first published review was of Abortion: Law, Choice, and Morality (1970). Callahan's latest book, The Five Horsemen of the Modern World: Climate, Food, Water, Disease, and Obesity, is a sustained and detailed explanation of a series of challenges facing humankind in this century. Callahan's prognosis is bleak, his analyses credible, and while hope is not lost, the moral of the story is that we had better get our act together fast. Callahan argues that when we face challenges like these, rational persuasion is insufficient. Human emotions must be engaged. Without knowledgeable emotional engagement by millions of people, we are done for. It seems to me that he is really calling for a national cultural conversion experience, rather as, almost three hundred years ago, Jonathan Edwards declared that if there is a hell, it makes good sense to frighten people out of it!